2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Active compression-decompression cardiopulmonary resuscitation (CPR) versus standard CPR for cardiac arrest patients: a meta-analysis

Abstract: BACKGROUND: Active compression-decompression cardiopulmonary resuscitation (ACD-CPR) has been popular in the treatment of patients with cardiac arrest (CA). However, the effect of ACD-CPR versus conventional standard CPR (S-CRP) is contriversial. This study was to analyze the effi cacy and safety of ACD-CPR versus S-CRP in treating CA patients. METHODS:Randomized or quasi-randomized controlled trials published from January 1990 to March 2011 were searched with the phrase "active compression-decompression cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
(32 reference statements)
0
9
1
1
Order By: Relevance
“…Mechanical devices designed to improve efficiency of chest compression have not consistently improved out-of-hospital cardiac arrest outcomes and are not recommended for routine use. [14][15][16][17] Failure of these devices to improve patient outcomes when applied broadly does not exclude a potential benefit during prolonged resuscitation or invasive procedures when rescuer fatigue could compromise quality of CPR.…”
Section: Interventionsmentioning
confidence: 99%
“…Mechanical devices designed to improve efficiency of chest compression have not consistently improved out-of-hospital cardiac arrest outcomes and are not recommended for routine use. [14][15][16][17] Failure of these devices to improve patient outcomes when applied broadly does not exclude a potential benefit during prolonged resuscitation or invasive procedures when rescuer fatigue could compromise quality of CPR.…”
Section: Interventionsmentioning
confidence: 99%
“…[12] The quality of cardiopulmonary resuscitation depends on the suffi ciency of the knowledge of health professionals and facilities. [13][14][15][16] Increasing survival of patients from cardiopulmonary arrest requires improvement in resuscitation education. [17][18][19][20][21][22][23][24] Studies conducted in Iran and New Zealand showed that the knowledge of interns and newly qualifi ed doctors were substandard.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that ACD CPR does not provide significant benefits over standard CPR. 16 Another meta-analysis by Wang et al suggested that the ACD CPR device is difficult to adhere to the patient's chest during resuscitation. 17 …”
Section: Flaws With Using Acd Cpr Alonementioning
confidence: 99%